TAVR: A Review of Current Practices and Considerations in Low-Risk Patients - Jenna Spears; Yousif Al-Saiegh; David Goldberg; Sina Manthey; Sheldon Goldberg (Journal of Interventional Cardiology)
Transcatheter aortic valve replacement (TAVR) is an established treatment for severe, symptomatic, aortic stenosis (AS) in patients of all risk categories and now comprises 12.5% of all aortic valve replacements. TAVR is a less invasive alternative to traditional surgical aortic valve replacement (SAVR), with equivalent or superior outcomes. The use of TAVR has increased rapidly. The success and increase in use of TAVR are a result of advances in technology, greater operator experience, and improved outcomes. Indications have recently expanded to include patients considered to be at low risk for SAVR. While TAVR outcomes have improved, remaining challenges include the management of coexistent coronary artery disease, prevention of periprocedural stroke, and issue of durability. These issues are even more relevant for low-risk, younger patients.